1991
DOI: 10.3354/meps079195
|View full text |Cite
|
Sign up to set email alerts
|

Species composition shift of confined bacterioplankton studied at the level of community DNA

Abstract: ABSTRACT. Using a new DNA hybridization technique that does not require culturing, we compared the species composition of natural planktonic bacterial assemblages before and after confinement in 20 1 containers for ca 2 d Although confinement is known to cause species shifts, possibly by stimulating growth of certain types of cells near the container wall, we found that such shifts were minor; 5 to 15 % of the communities had changed during confinement. The greatest shifts occurred in the samples that had the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 19 publications
0
30
1
1
Order By: Relevance
“…This is because >99% of bacteria in typical native heterotrophic bacterial communities are nonculturable on standard media (Ferguson et al, 1984;Lee and Fuhrman, 1991): hence, bacteria used as bioassay organisms are probably not representative of the natural microbial community. Additionally, even minor differences between host strains can sometimes affect susceptibility to phage infection (Ackermann and DuBow, 1987), resulting in a minimum estimate of phage abundance for a particular species.…”
Section: Natural Marine Virus Communitiesmentioning
confidence: 99%
“…This is because >99% of bacteria in typical native heterotrophic bacterial communities are nonculturable on standard media (Ferguson et al, 1984;Lee and Fuhrman, 1991): hence, bacteria used as bioassay organisms are probably not representative of the natural microbial community. Additionally, even minor differences between host strains can sometimes affect susceptibility to phage infection (Ackermann and DuBow, 1987), resulting in a minimum estimate of phage abundance for a particular species.…”
Section: Natural Marine Virus Communitiesmentioning
confidence: 99%
“…Filtration at 0.2 pm may let bacteria through (Zimmerman 1977, Tabor et al 1981, McDonnell & Hood 1982, Li & Dickie 1985Stockner et al 1990). It is also known that filtration at 0.6 or 0.8 pm may both let flagellates through (Fuhrman & McManus 1984, Cynar et al 1985 and sizeselect the community composition of the bacterial community, and several studies have evidenced shifts in community taxonomic composition after filtration and enclosure of bacteria (Ferguson et al 1984, Lee & Fuhrman 1991. Furthermore, some filters may retain dissolved organic matter (Maske & Garcia-Mendoza 1994), thus making the sample less rich in nutrients, while other filters may allow the breakage of some fragile cells, thus enriching the sample (Ferguson et al 1984, Goldman & Dennett 1985, Fuhrman & Bell 1985.…”
Section: Introductionmentioning
confidence: 99%
“…Yentsch 1957, Nagata 1986, Venrick et al 1987, Stramski 1990; the concentration of bacteria for enumeration (Kepner & Pratt 1994) or for acid nucleic diversity studies (e.g. Lee & Fuhrman 1991); the generation of bacteria-free and predator-free water used, for example, for dilution-growth experiments (Kirchman et al 1982, Wright & Coffin 1984, Li & Dickie 1985; fractionation for sizespecific metabolism estimates (e.g. Azam & Hodson 1977, Palumbo et al 1984, Gnffith et al 1990, Joint et al 1993 or the separation of functional components of the microbial plankton (Larsson & Hagstrom, 1982) and the corresponding uncoupling of the microbial food web (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A crucial assumption of these long-term experiments is that the growth of the prokaryotic assemblage is harmonic, i.e., all natural populations grow proportionally and species composition does not change during the incubation. Previous studies have shown a dramatic increase in culturability (ZoBell 1943;Ferguson et al 1984) and average metabolic activity (Sherr et al 1999b) of marine bacteria during bottle incubations, although these effects seemed minimized in large volume incubations (ZoBell 1943;Lee and Fuhrman 1991). Recent data indicate that predator removal can affect bacterial composition (Suzuki 1999), especially if the assemblage was previously under a strong grazing pressure (Simek et al 1999).…”
mentioning
confidence: 99%